Customer satisfaction towards the facilities management services at the Plaza Merdeka shopping mall, Kuching - Awang Yunus, Awang Ihsan (2013)
Shopping centers industry has grown considerable in Malaysia. Nevertheless, the growth is not only seen in the numbers of shopping centers development but also in the size and format. Today, this sector is identified as a major contributor to the Malaysia economy. Moreover, the success or failure of shopping centers depends on many factors; but the customer satisfaction is one of the factors considered vital to its success. Consequently, it is important to understand the level of customer satisfaction towards shopping centers and how facilities management can add value to the management of shopping centre. The aim of the study is to evaluate customer satisfaction towards Facilities Management (FM) services at shopping mall. The data was collected through the literature study, questionnaire survey and also interviews from the shopping mall management. 50 questionnaires was distributed and 45 were returned duly answered by the respondents on the survey conducted According to the findings, Building Operation and Maintenance has the highest average index of customer satisfaction level with 3.8 or 22%. Based on the analysis, suggested improvements were recommended. As a conclusion, the 3 objectives were achieved and recommendations for future study were suggested